EFL Junior High School Students’ Learning Style - Ramaniya, Made Ananda (STKIP AGAMA HINDU SINGARAJA, 2021)
The current study investigated EFL students’ learning style. The study was a survey study followed by 30 junior high school students in Singaraja Bali. In identifying students’ learning style, the updated Index of Learning Styles (ILS) developed by Felder and Silverman (1988) was used. The result of data analysis found that the majority of students prefer visual (76.7%), active (66.7%), sensing (60%), and global (53.3%). The result of this study implied that teachers should adjust their way of teaching to accommodate students’ learning style. They can apply various learning media such as video, animated pictures to motivate the students in learning.